On Street Parking Effect To Performance Of The Imam Bonjol Street In Palu City - Nita Ayu Lestari; Rahmatang Rahman; Anas Tahir (Politeknik Negeri Ujung Pandang, 2021)
Traffic jam caused by a lots of vehicles which parked on the road has always been a problem on urban roads. The lack of parking facilities out of the road and a lot of generation due to public facilities such as bank, restaurants, pharmacies, shops, and health center, will have an impact on traffic jam on the Imam Bonjol road section. This research aim for determine the magnitude effect of parking on street to the road performance of the Imam Bonjol street. The data needed includes, highway geometric, collecting data obtained from the results of the surveys is data on traffic volume, side barriers, parking on the road data and speed data. The parking survey methods using plat number methods and the data was analysed using the MKJI 1997 calculation method. The results of this research indicate that parking on the road is affected the performance of the imam bonjol street. the amount of traffic volume on saturday at 20.00 - 21.00 WITA is 3034 vehicles/hour. Side barriers values obtained is 560.7 friction/hour with high conditions typical is commercial areas, high activities on the road side, so the value of capacity dropped from 4576 smp/hour before parking, to 2533 smp/hour after parking on the road. The value average speed of light vehicle on Saturdays for the west to east is 24,42 km/hour, while the east to west is 23,94 km/hour. In 2018 the DS value is 0.65 with the level of service C. Whereas in 2023 the performance increased to DS = 1,23 with the level of service F.